An Overview of Mucoadhesive Thermoreversible Nasal Gel - Thakur, Rakesh; Sharma, Abhishek (Asian Journal of Pharmaceutical Research and Development, 2021)
Nasal drug is a supportive delivery technique to acquire therapeutic related levels of the medicine in the blood and an sufficient bioavailability. The Drugs have been nasally administrated for entertaining and therapeutic function since premature period. Administration through Nasal route offers a striking route of drug administration for achieving total systemic drug effects to the oral and parenteral route. Nasal drug delivery include rather the large surface area of the nasal cavity and which promotes quick absorption and relatively high blood flow. To improve nasal drug absorption many attempts have been completed in the recent years to develop the residence time of therapy formulations in the nasal cavity. To get better nasal drug absorption many attempts have been completed in the recent years to enhance the residence time of remedy formulations in the nasal cavity, out of them thermoresponsive in situ gel formulation approaches are one of the very important and effective.